2009
DOI: 10.48550/arxiv.0907.5245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A possible mechanism of energy dissipation in the front of a shock wave driven ahead of a coronal mass ejection

M. Eselevich,
V. Eselevich

Abstract: Mark 4 and LASCO C2, C3 coronagraph data analysis shows that, up to the distance R ∼ 5 R ⊙ from the center of the Sun, the thickness of a CMEgenerated shock front may be of order of the proton mean free path. This means that the energy dissipation mechanism in a shock front at these distances is collisional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Within the experimental error, thickness δ * F ≈ 0.1-0.2 R ⊙ does not vary with distance and is determined by the LASCO C3 instrument spatial resolution. Transfer from the shock front with thickness δ F to the discontinuity with thickness δ * F ≪ δ F can be interpreted as transition from the collisional to collisionless shock wave [7]. Similar discontinuities in brightness profiles associated with collisionless shock waves were registered ahead fast halotype CMEs (V > 1500 km s −1 ) at distances > 10 R ⊙ in [11].…”
Section: On Possibility For Resolution Of a Shock Front Widthmentioning
confidence: 59%
“…Within the experimental error, thickness δ * F ≈ 0.1-0.2 R ⊙ does not vary with distance and is determined by the LASCO C3 instrument spatial resolution. Transfer from the shock front with thickness δ F to the discontinuity with thickness δ * F ≪ δ F can be interpreted as transition from the collisional to collisionless shock wave [7]. Similar discontinuities in brightness profiles associated with collisionless shock waves were registered ahead fast halotype CMEs (V > 1500 km s −1 ) at distances > 10 R ⊙ in [11].…”
Section: On Possibility For Resolution Of a Shock Front Widthmentioning
confidence: 59%
“…Given u > u C , a shock wave with front thickness δ F was formed in the frontal part of the disturbed region. In [3] also was shown that the coordinate system connected with the CME's frontal structure was best suited for demonstrating differences of the disturbed region, reflecting the presence or absence of a shock wave. Moreover, the possibility of relatively accurate measurements of δ F in the solar corona with Mark 4 and LASCO C2 was justified.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important parameters of the shock front is its thickness δ F , since it contains information about the energy dissipation mechanism in the shock wave. Analysis in [2,3] showed that it is possible to measure the shock front thickness δ F correctly with Mark 4 and LASCO C2 data. Due to measurement results, an experimental dependence δ F (R) was constructed for eight CMEs with velocities u > u C (upper curve made-up of symbols labelled as δ F in Figure 1).…”
mentioning
confidence: 98%
See 1 more Smart Citation